PERGESERAN DOMINANSI SPESIES GULMA PADA PERKEBUNAN KELAPA SAWIT SETELAH APLIKASI HERBISIDA SISTEMIK - Araz Meilin (Jurnal Ilmiah Universitas Batanghari Jambi, 2008)
This research aims at identification of 1) weeds domination in palm oil plantation prior to herbiside treatment and 2) displcement of domination of weed species after systemic treatment of herbiside. This research was conducted at peoples plantation area petaling jaya village, district of sungai gelam, regency of muaro jambi, province of jambi. Herbiside applied was with active isprophil amina gliphosate,2.4 D dimetiamina, and triasulphuron 75 %. Analysis of weed vegetation data was SDR value. The result of the analysis shours that there are 5 species that dominate. The 5 species are imperata cylindrica with SDR value 27,8%, Asystasia intrusa (9,4%), melastoma affinae (9,2%), panicum repens (8,2%), and boreria alato (7,7%). The application of herbiside with different active substance shows different displacement of weed domination..